Predictive capacity of the academic procrastination scale in university students - Loayza-Maturrano, Edward Faustino (2021)
The objective of this research is to determine the predictive capacity of the academic procrastination scale in university students regarding their academic performance. The methodology used in this study is quantitative, correlational-cross-sectional. The Solomon and Rothblum (1984) academic procrastination questionnaire was applied to 74 students distributed in three courses (language and communication, technical writing and textual comprehension) of the Universidad Nacional Agraria La Molina. The results showed that 31.9% of students have academic procrastination between the scales "always" or "almost always". Furthermore, 45.15% of the students stated that frequent or moderate academic procrastination had caused them academic problems. There was a significant inverse correlation between academic procrastination and academic performance of university students (p <0.01). Also, male students showed higher levels of procrastination than females (p <0.01). This study concludes that students who show high levels of academic procrastination show lower academic performance or drop out of the course.